TOPIC OF THE ARTICLE: BENEFITS OF KNOWING ENGLISH FOR STUDENTS. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
English has become one of the most important global languages in education, science, technology, and communication. For students, knowing English provides numerous academic and personal advantages. It enables access to a wide range of educational resources, including textbooks, research articles, and online courses that are mainly available in English. Moreover, English proficiency improves students’ communication skills, critical thinking, and confidence. This article discusses the key benefits of learning English for students, focusing on academic success, career opportunities, and global integration.